Tuberculosis and chronic hepatitis B virus infection in Africans and variation in the vitamin D receptor gene. - Bellamy, R; Ruwende, C; Corrah, T; McAdam, K; Thursz, M; Whittle, H; Hill, A (1999)
The active metabolite of vitamin D, 1,25 dihydroxyvitamin D3, is an important immunoregulatory hormone [1]. Its effects are exerted by interaction with the vitamin D receptor, which is present on human monocytes and activated T and B lymphocytes. Variation in the vitamin D receptor gene was typed in 2015 subjects from large case-control studies of three major infectious diseases: tuberculosis, malaria, and hepatitis B virus. Homozygotes for a polymorphism at codon 352 (genotype tt) were significantly underrepresented among those with tuberculosis (chi2=6.22, 1 df, P=. 01) and persistent hepatitis B infection (chi2=6.25, 1 df, P=.01) but not in subjects with clinical malaria compared with the other genotypes. Therefore, this genetic variant, which predisposes to low bone mineral density in many populations, may confer resistance to certain infectious diseases.